A new energy conservation scheme for the numeric study of the heat transfer in profile extrusion calibration - Marques, Filipe (2017)
In this work, a new second-order conservative finite volume scheme using the cell-to-vertex interpolation is proposed to solve the heat transfer problem involving discontinuous solution and discontinuous materials properties. We apply the method to a thermoplastic extrusion process where a dry calibration is used to cool down a polymer tape. One of the major difficulties in the modelling is to prescribe the adequate value for the heat transfer coefficient between the polymer and the calibrator. To this end, we define an optimization procedure coupled with the new finite volume method to evaluate the heat transfer coefficient at the polymer-calibrator interface from experimental data.